Digital storytelling in a classroom a case study on grade 5 pupil's reception of digital storytelling as storytelling approach - Garcia, Duchess C.
Digital storytelling in a classroom: a case study on Grade 5 pupils' reception of digital storytelling as storytelling approach is conducted to determine the students' reception towards the process of digital storytelling through lectures, workshops and story assessment. The study aimed to introduce the process of utilizing media elements such as images, music, texts, and effects and teach grade 5 students the method of creating a Digital story. The reception and treatment of the students towards the process is determined with the use of the Digital Storytelling Rubric. The study is also supported by the theory Uses and Gratifications which explains the relationship of media to its audiences and consumers. There were 18 stories made by the students and were assessed using the rubric of digital storytelling with corresponding scores and evaluation. Furthermore, the study concluded that the students were able to adapt the process of Digital storytelling. The process can be helpful for students as well as teachers to develop their skills in utilizing media
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts